Histone acetylation regulates prostate ductal morphogenesis through a bone morphogenetic protein–dependent mechanism. Issue 11 (2nd September 2015) - Keil, Kimberly P.; Altmann, Helene M.; Abler, Lisa L.; Hernandez, Laura L.; Vezina, Chad M.
<x xml:space="preserve">Abstract</x> Background: Epigenetic factors influence stem cell function and other developmental events but their role in prostate morphogenesis is not completely known. We tested the hypothesis that histone deacetylase (HDAC) activity is required for prostate morphogenesis. Results: We identified the presence of class I nuclear HDACs in the mouse urogenital sinus (UGS) during prostate development and found that Hdac 2 mRNA abundance diminishes as development proceeds which is especially evident in prostatic epithelium. Blockade of HDACs with the inhibitor trichostatin A (TSA) decreased the number of prostatic buds formed in UGS explant cultures but not the number of buds undergoing branching morphogenesis. In the latter, TSA promoted an extensive branching phenotype that was reversed by exogenous NOGGIN protein, which functions as a bone morphogenetic protein (BMP) inhibitor. TSA also increased Bmp2 promoter H3K27ac abundance, Bmp2 and Bmp4 mRNA abundance, and the percentage of epithelial cells marked by BMP‐responsive phosphorylated SMAD1/5/8 protein. TSA exposed UGS explants grafted under the kidney capsule of untreated host mice for continued development achieved a smaller size without an obvious difference in glandular histology compared with control treated grafts. Conclusions: These results are consistent with an active role for HDACs in shaping prostate morphogenesis by regulating Bmp abundance. Developmental Dynamics 244:1404–1414, 2015. © 2015 Wiley Periodicals, Inc.